Implementation of Good Food Production Method for Kerupuk Household Industry in Sidoarjo - Arif Herlambang; Endah Asmawati; Yon Haryono (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
The owners of SME kerupuk Sidoarjo so far still glued to the traditional concept, that is only focus on the fulfillment of quantity, while the quality factor is still not the main focus. In order to compete in the era of free market, SME kerupuk Sidoarjo must give main focus on food quality. The focus of food quality improvement can be done through the fulfillment of food quality requirements by applying Good Food Production Methods for Household Industries (GFPM-HI). The implementation of GFPM-HI was conducted on two SMEs Sidoarjo, namely UD Dua Kelapa and Sinar Jaya. The process of applying GFPM-HI, starting from the process of identifying gender analysis pathway (gap), designing compliance requirements, implementation, and evaluation process. The evaluation results still have some criteria that have not been optimal. Overall, the process of applying CPPB-IRT UD Dua Kelapa and Sinar Jaya shows an increase in compliance scores of more than 40%.